Cash holdings and employee welfare - Ghaly, Mohamed; Dang, Viet Anh; Stathopoulos, Konstantinos (Journal of Corporate Finance, 2015)
This paper examines the relation between employee welfare practices and corporate cash holdings. We find firms that are strongly committed to employee well-being, measured by ratings on employee relations, to hold more cash. The effect of employee welfare standards on cash holdings is stronger for firms in human-capital-intensive, competitive, and high-labor-mobility industries in which employees are more important to their businesses. These results are consistent with the predictions of the stakeholder theory. Overall, our paper provides novel evidence on the role human capital and employee relations play in a firm's cash management policy.